A two-dimensional model of a solid-state regenerator based on combined electrocaloric-elastocaloric effect. (September 2017) - Aprea, Ciro; Greco, Adriana; Maiorino, Angelo; Masselli, Claudia
Abstract: Solid-state refrigeration technologies are considered nowadays emerging alternative to vapor compression refrigeration. In this paper is introduced a two-dimensional model of solid-state refrigerator, which employs materials experiencing a combined electrocaloric-elastocaloric effect and it operates at room temperature. A numerical investigation is performed to explore the energetic performance of the refrigerators. The results reveal that PbTiO3 as elastocaloric refrigerant confers the best performances in terms of COP; the highest cooling power estimated are proper of combined elastocaloric-electrocaloric effect, with increments around +65% than employing PbTiO3 in single electrocaloric/elastocaloric refrigeration, on equal operative conditions.